Does working with industry come at a price? A study of doctoral candidates' performance in collaborative vs. non-collaborative Ph.D. projects. (July 2015) - Salimi, Negin; Bekkers, Rudi; Frenken, Koen
Abstract: Collaborative Ph.D. projects between university and industry constitute an important aspect of university–industry collaboration, yet has remained under-researched thus far. The specific question this paper asks is how collaborative Ph.D. projects perform compared to non-collaborative Ph.D. projects. Conducting an empirical study on 448 Ph.D. projects at Eindhoven University of Technology, it is observed that collaborative Ph.D. projects outperform non-collaborative Ph.D. projects both in terms of industrial performance (number of patents and patent citations) and academic performance (number of publications and publication citations). A further investigation indicates that the high performance of collaborative Ph.D. projects is specific to the university׳s collaborations with Philips and with Public Research Organisations. When measuring academic performance is a more restricted manner by looking at top-publications only, it is observed that collaborative Ph.D. projects no longer outperform non-collaborative Ph.D. projects. One of the policy implications of this study is that there seems to be no reasons for universities to be reserved to enter into collaborative Ph.D. projects, when such opportunities arise. Highlights: The effect of industry collaboration on the academic performance of Ph.D.'s is investigated. We test this effect by an empirical study on 448 Ph.D. projects. Ph.D.'s in collaborative projects achieve a higher performance than non-collaborative peers. The increased performance strongly depends on collaborative partner. University supervision by a 'star scientist' makes considerable difference on performance.